Identification of diagnostic gene biomarkers related to immune infiltration in patients with idiopathic pulmonary fibrosis based on bioinformatics strategies - Dai, Xiangdong; Yang, Zhihua; Zhang, Wenjing; Liu, Shuai; Zhao, Qianru; Liu, Tao; Chen, Lu; Li, Lin; Wang, Yi; Shao, Rui (Frontiers in Medicine, 2022)
Objective: This study predicts the identification of potential diagnostic markers of idiopathic pulmonary fibrosis (IPF) and analyzes the significance of immune cell infiltration in this pathology. Methods: Two publicly available gene expression profiles (GSE10667 and GSE24206 datasets) from 48 IPF samples and 21 control samples from humans were downloaded from the GEO database and differentially expressed genes (DEGs) were screened from them. Use The Lasso regression model and support vector machine recursive feature elimination (SVM-RFE) analysis was used to identify candidate biomarkers. The area under the subject's work characteristic curve (AUC) value is obtained to assess its recognition ability. The expression levels and diagnostic value of biomarkers in IPF were further validated in the GSE53845 dataset (40 IPF patients and 8 control groups). Comprehensive analysis of immune infiltrated cells of IPF was performed using R software and immune cell infiltration estimation analysis tool- deconvolution algorithm (CIBERSORT). Results: A total of 43 DEGs were identified. The identified DEGs mainly involve pneumonia, lung disease, collagen disease, obstructive pulmonary disease and other diseases. Compared with the control group, there were differences in the activation of IL-17 signaling pathways, amoebic disease, interaction of viral proteins with cytokines and cytokine receptors, protein digestion and absorption, and flaccid hormone signaling pathways in IPF. CRTAC1, COL10A1, COMP, IGFL2, NECAB1, SCG5, SLC6A4, and SPP1 are diagnostic markers of IPF. Immune cell infiltration analysis showed that CRTAC1, COL10A1, COMP, IGFL2, NECAB1, SCG5, SLC6A4, and SPP1 were associated with monocytes, plasma cells, neutrophils, and regulatory (treg) T cells. Conclusion: CRTAC1, COL10A1, COMP, IGFL2, NECAB1, SCG5, SLC6A4 and SPP1 can be used as diagnostic markers for IPF, providing new ideas for the future study of IPF occurrence and molecular mechanisms.